Updated Nematocyst Types in Tentacle of Venomous Box Jellyfish, Chironex indrasaksajiae (Sucharitakul, 2017) and Chiropsoides buitendijki (Horst, 1907) (Cnidaria, Cubozoa) in Thai Waters - Thippawan Yasanga; Klintean Wunnapuk; Rochana Phuackchantuck; Lakkana Thaikruea; Thunyaporn Achalawitkun; Purinat Rungraung; Sineenart Santidherakul (Toxins)
The multiple-tentacle box jellyfish, Chironex indrasaksajiae (Sucharitakul, 2017) and Chiropsoides buitendijki (Horst, 1907), are venomous species found in Thai waters. They are responsible for numerous envenomations through their stinging organelles, nematocysts. These specialized microscopic structures discharge venom, yet detailed knowledge of their types and morphology in these species remains limited. This study updates the characterization of nematocyst types and features in C. indrasaksajiae and C. buitendijki using light and scanning electron microscopy for detailed examination. Four distinct nematocyst types were identified: banana-shaped microbasic p-mastigophores, oval-shaped microbasic p-rhopaloids, sub-spherical microbasic p-rhopaloids, and rod-shaped isorhizas. In C. indrasaksajiae, banana-shaped microbasic p-mastigophores exhibited significant intraspecific variability, ranging from 30.26 µm to 102.56 µm in length and 6.42 µm to 17.01 µm in width. Conversely, C. buitendijki showed a narrower size range, 72.17 µm to 98.37 µm in length and 10.73 µm to 16.48 µm in width, based on multiple individuals. The size ranges for the other nematocyst types were consistent across both species. This study enhances the understanding of nematocyst morphology in these box jellyfish, providing a foundation for further research on venom delivery mechanisms and improved management of jellyfish envenomations in Thai waters.